Resilience and Cognitive Function in Patients With Schizophrenia and Bipolar Disorder, and Healthy Controls - Deng, Mengjie; Pan, Yunzhi; Zhou, Li; Chen, Xudong; Liu, Chang; Huang, Xiaojun; Tao, Haojuan; Pu, Weidan; Wu, Guowei; Hu, Xinran; He, Zhong; Xue, Zhimin; et al. (Frontiers in Psychiatry, 2018)
Background: This study compared adaptive resilience among patients with schizophrenia, bipolar disorder and healthy controls, and examined the relationship of resilience to cognitive function. Methods: A sample of 83 patients diagnosed with schizophrenia, 35 with bipolar disorder, and 52 healthy controls completed the Connor-Davidson Resilience Scale (CD-RISC) and cognitive tests of verbal comprehension, executive functioning and working memory. Paired comparison of diagnostic groups on CD-RISC and cognitive tests was conducted. Linear regression was used to identify the independent association of clinical diagnoses and neurocognition with resilience deficits. Results: Both patient groups showed significantly lower CD-RISC scores and poorer cognitive function than healthy controls and the schizophrenia group scored lower than bipolar group on these measures as well. CD-RISC scores were positively correlated with all three cognitive measures in the entire sample but not within the diagnostic samples. Multiple regression analysis showed differences in CD-RISC between diagnostic groups were not mediated by differences in these three measures of neurocognition. Discussion: Schizophrenia and bipolar disorder are associated with impairments in both resilience and cognitive function but the impairment in resilience appears to be independent of deficits in cognitive function measured here and may reflect unmeasured dimensions of cognitive function, other impairments or environmental factors.